Analysis of an online taekwondo competition - Asenov, A. (Pedagogy, 2020)
The state of emergency declared in Bulgaria due to the COVID-19 situation has demonstrated that practicing sport under these conditions is limited. The National Sport Academy "Vassil Levski" has been the pioneer in the online trainings in Bulgaria. The Taekwondo department of the Academy was the first one to introduce an online competition in taekwondo during the 2020 pandemic in Bulgaria. The methods we used were theoretical - analytical, expert evaluation, mathematical - statistical method and survey. The feedback from the participants in the online tournament clearly indicate that such an event can and must be used in order to maintain motivation in athletes. Such an event cannot fully replace the "real" competition but it is essential under the conditions of social isolation.